Investigation of suppression of Υ⁡ (nS) in relativistic heavy-ion collisions at √sNN= 200 GeV and 5.02 TeV - Kim, Junlee; Park, Jaebeom; Hong, Byungsik; Hong, Juhee; Kim, Eun-Joo; Kim, Yongsun; Kweon, MinJung; Lee, Su Houng; Lim, Sanghoon; Seo, Jinjoo (Physical review, 2025)
The primary purpose of studying quarkonium production in relativistic heavy-ion collisions is to understand the properties of the quark-gluon plasma. At various collision systems, measurements of quarkonium states of different binding energies, such as Υ⁡(𝑛⁢𝑆), can provide comprehensive information. A model study has been performed to investigate the modification of Υ⁡(𝑛⁢𝑆) production in Pb-Pb collisions at √𝑠𝑁⁢𝑁=5.02TeV and Au-Au collisions at √𝑠𝑁⁢𝑁=200GeV. A Monte Carlo simulation study is performed with a publicly available hydrodynamic simulation package for the quark-gluon plasma medium and a theoretical calculation of the temperature-dependent thermal width of Υ⁡(𝑛⁢𝑆) considering the gluodissociation and inelastic parton scattering for dissociation inside the medium. In addition, we perform a systematic study with different descriptions of initial collision geometry and formation time of Υ⁡(𝑛⁢𝑆) to investigate their impacts on yield modification. The model calculation with a varied parameter set can describe the experimental data of Υ⁡(𝑛⁢𝑆) in Pb-Pb collisions at 5.02 TeV and Υ⁡(2⁢𝑆) in Au-Au collisions at 200 GeV but underestimates the modification of Υ⁡(1⁢𝑆) at the lower collision energy. The nuclear absorption mechanism is explored to understand the discrepancy between the data and simulation.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 04.08.2025